EP081/#1043 Cervical cancer treated by neoadjuvant chemotherapy followed by radical surgery: a case series from mirebalais, Haiti. (4th December 2022) - Millien, Christophe; Henderson, Rebecca; Hubert, Jean Joel Saint; Ulysse, Jean-Claude; Triedman, Scott; Fadelu, Temidayo; Slater, Sarah; Mckenzie, Nathalie; Mutombo, Alex; Lormil, Joarly; Randall, Tom
Abstract : Objectives: In Haiti, a low-resource setting where radiotherapy is unavailable, significant numbers of women present with locally advanced cervical cancer in need of treatment. We built a multidisciplinary team to collaboratively implement neoadjuvant chemotherapy followed by surgery, and aimed to retrospectively assess the efficacy and feasibility of this approach. Methods: We implemented paclitaxel/carboplatin neoadjuvant chemotherapy (NACT) followed by radical surgery for women with stage IB2-IIA cervical cancer at the Hospital Universitaire de Mirebalais (HUM). Three Haitian gynecologists worked remotely with expert clinicians to pilot the program. We aimed to determine the feasibility and safety of this approach in this resource limited setting. Results: Between January of 2021 and May of 2022, 26 of 310 women diagnosed with cervical cancer at HUM received NACT followed by radical surgery. Women in the pilot sample were ages 38 to 69 years. Twenty-three received six cycles of chemotherapy, while the remainder received three cycles. As of May 2022, 16 had undergone radical surgery, three were lost to follow-up during chemotherapy, two were inoperable, and five were receiving chemotherapy. Of women undergoing radical surgery, two were found to have metastatic disease during surgery and one was found to have a recurrence of disease. There were no perioperative deaths. One woman experienced sepsis and developed a vesicovaginal fistula. Conclusions: Preliminary results suggest that NACT followed by radical surgery is feasible and safe in a resource limited setting, and may improve the chance for cure for women who otherwise might be offered comfort measures only.